Distribution and sources of organic matter in surface sediments of Bohai Sea near the Yellow River Estuary, China. (5th November 2015) - Liu, Dongyan; Li, Xin; Emeis, Kay-Christian; Wang, Yujue; Richard, Pierre
Abstract: Total organic carbon (TOC) and total nitrogen (TN) concentrations and C and N stable isotope compositions in 64 surface sediment samples from the mouth of the Yellow River (YR) and from the Bohai Sea (BS) outline the distribution and sources (terrestrial and marine) of sediment organic matter. Comparatively high TOC (0.5–0.9%) and TN (0.07–0.11%) concentrations in the Central BS correlate with fine-grained sediments that contain high concentrations of algal-derived organic carbon (AOC) and biogenic silica (BSi). Together, they indicate a dominant contribution of autochthonous organic matter from marine primary production. Low TOC (<0.2%) and TN (<0.03%) contents characterize surface sediments in the Bohai Strait and are typically associated with coarse-grained sediments of low AOC and BSi contents. δ 13 C values (−21 to −22‰) are characteristic of marine-derived organic carbon in the Central BS and the Bohai Strait, whereas a significant terrigenous contribution of 40–50% is indicated by lower values (<−23‰) near the YR mouth. The spatial pattern of rising δ 13 C from the YR mouth to offshore areas indicates rapid sedimentation of fluvial suspensions within the vicinity of the river mouth and in Laizhou Bay, so that only approximately 10–20% of YR-derived sediments are transported to and deposited in the Central BS and/or the Bohai Strait. At most sites, δ 15 N values are in the typical range of marine organic matter produced from assimilation of marine nitrate by phytoplankton (5–5.5‰), but some relatively high values (6–7.28‰) mark the southern area of the Laizhou Bay as a significant sink of anthropogenic nitrogen.